Therapeutic intervention in fear of cancer recurrence in adult oncology patients: a systematic review - Paperák, Patrik; Javůrková, Alena; Raudenská, Jaroslava (Journal of cancer survivorship, 2023)
PURPOSE: The study aims to provide an updated overview of studies that show the impact of psychotherapeutic interventions on fear of cancer recurrence (FCR), to explore the relationship between FCR and related factors (psychological distress, well-being, anxiety, depression, fear, coping strategies, quality of life), and to identify the most effective therapeutic approaches in managing FCR. METHODS: Three databases were searched between January 2021 and April 2021 using the key words "fear of cancer recurrence - psychotherapy - intervention" following the a priori established PRISMA protocol. RESULTS: Thirteen studies were included in the final review. The database search identified 239 potential papers. After removing duplicates and irrelevant articles by title and language, population, and type of study, 13 articles were assessed for eligibility of the abstract, and 13 full-text articles were reviewed and included in this systematic review. The studies were mainly from the Netherlands (4 out of 13). Positive benefits of therapeutic interventions on FCR were reported. CONCLUSIONS: This research highlights challenges in using therapeutic approaches in dealing with FCR and its management. Therapeutic intervention is an effective means of managing not only FCR but also related factors (distress, well-being, quality of life). However, individual needs and preferences must be taken into consideration whilst choosing a therapeutic approach. Cognitive behavioural therapy (CBT), acceptance and commitment therapy (ACT), and mindfulness-based interventions are the most used approaches with CBT being the most effective, especially in a blended form (i.e. standard CBT combined with other self-help activities). IMPLICATIONS FOR CANCER SURVIVORS: The aim was to provide information about the most effective therapeutic approaches for coping with FCR.
Keywords: Neoplasm Recurrence, Local; Fear; dospělí; strach; kvalita života; přežívající onkologičtí pacienti; Acceptance and Commitment Therapy; lidé; terapie přijetí a odevzdání; Quality of Life; Adult; Cancer Survivors; lokální recidiva nádoru; Humans